SERANGGA-SERANGGA PADA TANAMAN GEDI (Abelmoschus manihot L.) DI DESA LOLAH DAN KALASEY KABUPATEN MINAHASA - Chendy Livinia Sambow; Jusuf Manueke; Redsway Maramis (COCOS, 2017)
ABSTRACTÂ  Plants Gedi is one type of horticulture type of vegetable can also be used as medicinal plants (Papodi et al, 2013) and is the type of vegetables typical of North Sulawesi, because it is a vegetable that is commonly used by the people of North Sulawesi as an ingredient for typical food from this area that Manado porridge, the field survey results show that the existence of some types of insects that attack plants Gedi. This causes a decrease in the quantity and quality of crops Gedi. This study aims to menngetahui types of insects on plants Gedi in the Village and Village Kalasey.Penelitian Lolah was conducted in two villages, in the village Lolah and Kalasey for three months from November 2016 to January 2017. This study used purposive sampling method in plants gedi in both villages. Each village was taken 4 locations. Sampling was conducted using an insect net and using tanagn. There are 4 orders were found, namely: the Order Hemiptera comprising two families (Family Pentatomidae and Family Plataspididae), Order Coleoptera consist of 5 Family (Family Chrysomelidae, Family Coccinelidae, Family Curculionidae, Family Buprastidae and Family Carabidae), Order Orthoptera (Family Acrididae) Order Lepidoptera (Pyralidae).